Finite element modeling and experimental validation of a radial extensometer and dependant z‐type self‐expanding endovascular stent. Issue 4 (13th December 2021) - Scott, Joel C. R.; Doman, Darrel A.; Johnston, Clifton R.
Abstract: Stent migration due to haemodynamic drag remains the primary cause of type I endoleak, potentially leading to aneurysm rupture. The prevalence of migration and endoleak can be partially attributed to deficiencies in stent‐graft radial spring design and a lack in understanding of the mechanical properties of endovascular stents. A converged finite element model of a custom radial extensometer was developed, fit, and validated using experimental results for bare stent wire ("uncovered") with outer diameter of 12 mm stent. During stent constriction to 50 % of the original cross‐sectional area, a comparison of experimental and modeled results produced an r 2 value of 0.946, a standard error of 0.099 N, and a mean percent error of 1.69 %. This validated finite element model can be used to analyze the mechanisms responsible for radial force generation in 316L stainless steel self‐expanding endovascular stents, as well as to evaluate new stent designs. Abstract : Stent migration due to haemodynamic drag remains the primary cause of type I endoleak, potentially leading to aneurysm rupture. The prevalence of migration and endoleak can be partially attributed to deficiencies in stent‐graft radial spring design and a lack in understanding of the mechanical properties of endovascular stents. This validated finite element model is was developed to analyze the mechanisms responsible for radial force generation in 316L stainless steel self‐expanding z‐type endovascular stents, as well as to evaluate new stent designs in the future.